MIGUEL GUITART - Behind Architectural Filters. Phenomena of Interference - Labarta Aizpún, Carlos (ZARCH, 2023)
Miguel GuitartBehind Architectural Filters. Phenomena of InterferenceNew York: Routledge, 2022. 302 pp. Tapa dura. Idioma: inglés. 36,26 €ISBN: 978-1-032-07748-2